2017
DOI: 10.1177/0886260517701450
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Risky Sexual Behaviors Among Sexual Minority Girls: Indirect Risk Pathways Through Peer Victimization and Heavy Drinking

Abstract: Sexual minority girls (SMGs), compared with heterosexual females, are more likely to report negative sexual outcomes including earlier age of sexual intercourse debut, more lifetime and recent sexual partners, pregnancy involvement, and sex while intoxicated. Data describing the mechanisms related to these health disparities are limited. The purpose of this study was therefore to longitudinally assess the roles of sexual minority-related peer victimization and heavy episodic drinking (HED) as mediators of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…Results regarding sexual orientation point to important directions for future investigation. In contrast to those in community-based samples (Dermody et al, 2017; Garofalo et al, 1998; Goodenow et al, 2008; Kann et al, 2016), non-heterosexual youth in this study were less likely than heterosexual youth to report ever having sex or engaging in high-risk sexual behavior. These findings may reveal important differences between non-heterosexual youth from justice-involved and community samples.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Results regarding sexual orientation point to important directions for future investigation. In contrast to those in community-based samples (Dermody et al, 2017; Garofalo et al, 1998; Goodenow et al, 2008; Kann et al, 2016), non-heterosexual youth in this study were less likely than heterosexual youth to report ever having sex or engaging in high-risk sexual behavior. These findings may reveal important differences between non-heterosexual youth from justice-involved and community samples.…”
Section: Discussioncontrasting
confidence: 95%
“…Research similarly suggests that non-heterosexual youth in community samples are more vulnerable to sexual risk behaviors and internalizing and externalizing problems compared to their heterosexual peers. Non-heterosexual youth tend to report earlier age of sexual debut and more sexual partners, inconsistent condom use, suicidality, and substance use (Dermody et al, 2017; Garofalo et al, 1998; Goodenow et al, 2008; Kann et al, 2016). However, Hirschtritt et al (2018) was unable to replicate some of the differences in sexual risk behaviors between non-heterosexual and heterosexual youth in a justice-involved sample.…”
Section: Sexual Orientation Differences In the Sexual And Mental Heal...mentioning
confidence: 99%
“…Regarding differences in self-relating processes, consistently with Hypothesis 2, we found higher levels of selfhate and self-inadequacy in sexual minority participants compared to heterosexual people. Negative and continuative experiences (e.g., direct and indirect discriminations) related to their sexual minority identity may represent a possible driver of these disparities (Dermody et al, 2020;Meyer, 2003;Puckett et al, 2015). Interestingly, both types of "negative self-relationship" (self-inadequacy and self-hate), and not only the most severe form of "negative" self-relationship (i.e., self-hate), are more prevalent in sexual minority people than heterosexual individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Dermody et al (2020) whit a longitudinal study, found that sexual minority-related victimization and heavy drinking may play important roles in explaining disparities in RSB among sexual minority girls: High levels of peer victimization among sexual minority girls predicted increased heavy episodic drinking, which was subsequently associated with RSB. Internalized sexual stigma, described as feelings of shame and low self-worth related to sexual minority identities (Herek et al, 2009), represented a significant predictor of psychological distress and mental health adverse outcomes among sexual minority people (Baiocco et al, 2015;Newcomb & Mustanski, 2010;Russell & Horn, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation